Optical properties of ternary thin films (Ni3Pb2S2) prepared by chemical bath deposition technique - Ho, Soon Min (World Research Journals, Indore, 2016)
Thin films of Ni3Pb2S2 were deposited on glass substrate from aqueous solutions of nickel (II) sulfate, lead (II) nitrate and sodium thiosulfate. In this work, tartaric acid acted as complexing agent. The films were studied using UV-Visible spectrophotometer in the range of 300-900 nm. The optical characterization indicates that the films have band gap that ranged between 1.2 - 1.5 eV.